Improvement of cell suspension cultures of transformed and untransformed Carica papaya cell lines, towards the development of an antiparasitic product against the gastrointestinal nematode Haemonchus contortus - Ortiz Caltempa, Anabel; Hernández, Marisela; Pérez, Ana Lilia; Aguilar, Liliana; Guzmán, Cynthia; Ayón-Núñez, Dolores Adriana; Fragoso, Gladis; Bobes, Raúl J.; López, Maria Eugenia; Sciutto, Edda; Villareal, María Luisa (Frontiers in Cellular and Infection Microbiology, 2022)
Parasitic diseases have a major impact on human and animal health worldwide. Despite the availability of effective anti-parasitic drugs, their excessive and uncontrolled use has promoted the emergence of drug resistance, severely affecting ecosystems and human health. Thus, developing environmentally friendly antiparasitic treatments is urgently needed. Carica papaya has shown promising effects against infectious diseases. C. papaya embryogenic calluses were genetically modified by our research team to insert immunogenic peptides with the goal of developing an oral anti-cysticercosis vaccine. Among these callus cell lines, one labeled as CF-23, which expresses the KETc7 immunogenic peptide, induced the highest protection levels against experimental cysticercosis. In the process of designing a natural antiparasitic product based on C. papaya that simultaneously induced immunity against cysticercosis, both transformed (SF-23) and untransformed (SF-WT) suspension cultures were produced and optimized. Our results showed a better duplication time (td) for SF-23 (6.9 days) than SF-WT (13.02 days); thus, the SF-23 line was selected for scale-up in a 2-L airlift bioreactor, reaching a td of 4.4 days. This is the first time that a transgenic line of C. papaya has been grown in an airlift bioreactor, highlighting its potential for scale-up cultivation in this type of reactor. Considering the previously reported nematocidal activity of C. papaya tissues, their activity against the nematode Haemonchus contortus of aqueous extracts of SF-WT and SF-23 was explored in this study, with promising results. The information herein reported will allow us to continue the cultivation of the transgenic cell suspension line of C. papaya under reproducible conditions, to develop a new anti-parasitic product.